Проблема легитимности карабахских ханов в контексте политической истории Шуши - Павел Чобанян (ՀՀ ԳԱԱ հրատ.)
Հրապարակվող երկու վավերագրերը նոր հնարավորություն են բացում Արցախի պատմության դեռևս մութ մի շարք հարցերի պարզաբանման համար: The publication of two documents provides us with an opportunity to shed a light on the hitherto unexplored issues dealing with the history of Artsakh.
Keywords: History; Political Science; D History; J Political Science